Interactions of some metal ions with Nitrogenous bases present in Nucleotides - Baghdad Science Journal (مجلة بغداد للعلوم)
Acidity constants at 30co and 0.125 ionic strength have been determined for the Nitrogous bases of nucleic acid; cytocine, uarcil and thymine, and found to be 3.55 x10-19 , 1.44 x10 -19 and 7.24 x10 -20 respectively. Stability constants of these bases with Thorium and uranyl ions have been determined. Results showed that metal ions Thorium and uranyl ions behave as hard acids and the nitrogenum bases behave as Hard bases according to Pearson's definition .Hardness – softness parameters for these ligands were calculated ,stability constants of complexes with metal ions could be arranged as follows :- Cytosine > Uracil > Thymine .